Avaliação comparativa das características estruturais e mecânicas de fios ortodônticos de NiTi e de suas propriedades funcionais - Allan Souza Portes (2017)
The aim of this study was to evaluate and compare the mechanical and structural properties of three different brands of NiTi orthodontic wires. The sample comprised of three superelastic (SE) and three thermoactivated (TA) rounded wires (.016and .018) of different sizes evaluating surface topography by scanning electron microscopy (SEM), elemental chemical composition by X ray diffraction spectroscopy (SEM/EDS) and present phases at room temperature by X ray diffraction (XRD), besides the evaluation of the mechanical properties through tensile and three point bending tests. All the tests were made with wires as received from the manufacturer. The XRD spectra allowed the identification of only the austenite, phase in all analyzed wires. Both B19' phase and R phase were not present in any of the samples analyzed. The wires characterization showed Ni and Ti in equal proportions. Forestadent wires presented the best finish surface, whilst all 3M and American Orthodontics wires presented roughness and longitudinal lines in the surface. The 3M superelastic wires showed less deflection if compared to the other SE wires. 3M SE wires reveled the largest unloading force. The American Orthodontics wires presented lower stress reorientation and should deliver lower intensity of forces during clinical use.